Spaces of transition: Young people’s social practices in Santa Cruz de Tenerife (Canary Islands, Spain) - Díaz-Rodríguez, Maria Carmen; Armas-Díaz, Alejandro; García-Herrera, Luz Marina; García-Hernández, Juan Samuel (DIE ERDE – Journal of the Geographical Society of Berlin, 2015)
Within the context of the growing interest in the study of young people in urban environments, the present article examines their relational spaces in a southern European city: Santa Cruz de Tenerife (Canary Islands, Spain) –with a view to identifying the places they frequent and establishing whether or not the most widely-used ones form a spatial network offering them different recreational opportunities. Combining quantitative and qualitative methods, the paper explores the social practices of young people. The information obtained reveals the significance of open public spaces and shopping malls for young people generally, although differences are seen in their practices according to age, gender and social background. The results also suggest that, in the routes they take and their stays in the aforementioned places, young people create a network of meeting spaces that owes more to the construction of their identity than to the existence of complementary formulas for recreation.